Alongshore sediment transport analysis for a semi-enclosed basin: a case study of the Gulf of Riga, the Baltic Sea - T. Soomere; T. Soomere; M. Z. Jankowski; M. Eelsalu; K. E. Parnell; M. Viška (Ocean Science)
The properties of wave-driven sediment transport and the dimensions of single sedimentary compartments are often radically different in different parts of semi-enclosed waterbodies with an anisotropic wind climate. The western, southern and eastern shores of the Gulf of Riga are a remote part of the more than 700 km long interconnected sedimentary coastal system of the eastern Baltic Sea from Samland in Kaliningrad District, Russia, to Pärnu Bay, Estonia. Even though shores of the gulf are generally straight or gently curved, the presence of small headlands and variations in the orientation of the coastline give rise to numerous fully or partially separated sedimentary compartments. We decompose sedimentary shores of this gulf into single compartments and cells based on the analysis of wave-driven potential sediment transport using high-resolution wave time series and the Coastal Engineering Research Centre (CERC) approach. The western shore of the Gulf of Riga forms a large interconnected sedimentary system with intense sediment transport that is largely fed by sand transported from the Baltic proper. The southern shore has much less intense sediment transport and is mostly an accumulation area. The south-eastern sector of the gulf is an end-station of counter-clockwise sand transport. The eastern shore consists of several almost isolated sedimentary cells and contains a longer segment where clockwise transport predominates. The transport rates along different shore segments show extensive interannual variations but no explicit trends in the period 1990–2022.